(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The mutual fund sectors are one of the fastest growing sectors in Indian Economy and have awesome potential for sustained future growth. Mutual funds make saving and investing simple, accessible, and affordable. The advantages of mutual funds include professional management, diversification, variety, liquidity, affordability, convenience, and ease of recordkeeping as well as strict government regulation and full disclosure. Financial markets are becoming more extensive with wide-ranging financial products trying innovations in designing mutual funds portfolio but these changes need unification in correspondence with investor’s expectations. Thus, it has become imperative to study mutual funds from a different angle, which is to focus on investor’s perception and expectations. This research paper focused attention on number of factors that highlights investors’ perception about mutual funds.